FACE LOCALIZATION WITH A CAMERA TO BE INTERFACED WITH IRIS SCANNER - TING, HENG NGUAN (IRC, 2019)
This system is an iris recognition system with a 2-dimensional robotic arm that can move to any given coordinate. The coordinate will be calculated based on the eyes and facial image that live captured from the camera. The arm system is based on two arms, two motors and a camera load. The first motor is attached to the base and turns the first arm. The second motor is attached to the first arm and rotates the second arm, which has a load attached to it. Once the arm had move to the desired location, a laptop will trigger the iris scanner to ask it to do the authentication process. If the biological data of the individuals had been verified, the laptop will send a set of data to Raspberry Pi through TCP/IP protocol to notify the system that the individuals can be verified.